'Asking for another' online: Membership categorization and identity construction on a food and nutrition discussion board. (June 2017) - Gordon, Cynthia; İkizoğlu, Didem
This discourse analytic study integrates theories of stance and membership categorization to investigate one online discussion thread initiated by a woman who asks for diet and health advice on behalf of her boyfriend, an interactive move we term 'asking for another'. Posters to the thread, in relatively explicit ways, construe the original poster as a 'nag' and 'mother-figure' and her boyfriend as a 'victim of nagging' and 'childish'. Our analysis illuminates how two features of the asking-for-another post (inadvertently) evoke these identities: (1) extreme case formulations, created via adjectives and adverbs, lead others to view the woman as inappropriately involved and controlling and her boyfriend as immature, and (2) details about the boyfriend's diet, provided via nouns and adjectives, index cultural ideologies of food and identity. This study illuminates the ambiguity and polysemy of the move of asking for another, contributing to research on identity construction and health-related advice-seeking online.